Improving 3RD Party Halal Local Service Providers in Halal Logistics: The Driving Factors from Malaysian F&B Manufacturing Perspectives - Ezanee Elias; Mohd Nasrun Mohd Nawi; Norlila Mahidin; Mohd Affendi Ahmad Pozin (International Journal of Supply Chain Management, 2019)
The paper aims to identify the determinants of driving factors from FB manufacturers, among the Small and Medium-sized Enterprises in Malaysia towards the acceptance of halal logistics services via 3rd party local service providers. The data for this quantitative study were obtained from 86 respondents via email approach. The research instrument was constructed from past studies and posted through Google Form and Gmail. The findings of this study exposed some important implications for academic's literature and practical for the halal logistics industry. The R2 value for the research model shows 0.724, indicating that 72.4% of the variance in the extent of the relationship can be explained by halal international logistics, the halal industry, and halal collaboration. Clearly, high demand from the international halal logistics, halal collaboration between the FB industrial sector and government agencies as well as high awareness of halal interests by customers are the factors that pressure on the SMEs to practice halal logistics services. Hopefully, the results of this study would contribute to the growth of research in the area of the halal industry.